Utilization of surfactant assisted zinc oxide nanodisk against breast cancer cells - Abdulsalam Alkhudhayri (Journal of Experimental Nanoscience)
The current work displayed the efficacy of the nanodisk shaped zinc oxide nanostructures (NDs-ZnONSs) processed via hydrothermal solution process and studies the cytotoxicity against human breast cancer cells (MCF-7). The NDs-ZnONSs were analyzed by using instruments such as X-ray diffraction pattern (XRD), Field emission scanning electron microscopy (FESEM), and Fourier transform infra-red spectroscopy (FTIR). The XRD and FESEM shows the crystallinity and morphology of NDs-ZnONSs states the estimated width size of each sheet diameter and length are ∼20-25 nm and 2-3 µm respectively. The cytotoxicity of MCF-7 cells with NDs-ZnONSs at different concentrations (1, 2, 5, 10, 25, 50 and 100 µg/mL) were examined via MTT and NRU assays. The results showed that at initial (1, 2 and 5 µg/ml) concentrations of NDs-ZnONSs didn’t show any cytotoxicity in cancer cells but higher concentrations (25, 50 and 100 µg/mL) of NDs-ZnONSs displayed a remarkable inhibition in cancer cells growth and morphology. Further, the reactive oxygen species (ROS) generation was also examined with NDs-ZnONSs at different concentrations and result showed that it increased with increasing the concentration of NDs-ZnONSs in MCF-7 cells. The expression of apoptotic genes (p53, bax, casp-3) including control via qRT-PCR, reveals that mRNA level of apoptotic genes with NDs-ZnONSs were upregulated.